Mother–Infant and Extra-Dyadic Interactions with a New Social Partner: Developmental Trajectories of Early Social Abilities during Play - Fadda, Roberta; Lucarelli, Loredana (Frontiers in Psychology, 2017)
Mother-infant interactions during feeding and play are pivotal experiences in the development of infants’ early social abilities (Biringen, 2000; Stern, 1985, 1995). Stern indicated distinctive characteristics of mother-infant interactions respectively during feeding and play, suggesting to evaluate both to better describe the complexity of such early affective and social experiences (Stern, 1996). Moreover, during the first years of life, infants acquire cognitive and social skills that allow them to interact with new social partners in extra-dyadic interactions. However, the relations between mother-child interactions and infants’ social skills in extra-dyadic interactions are still unknown. We investigated longitudinally the relations between mother-child interactions during feeding and play and child’s pre-verbal communicative abilities in extra-dyadic interactions during play. 20 dyads were evaluated at T1 (infants aged between 9-22 months) and 6 months later, at T2. The interdyadic differences in mother-infant interactions during feeding and play were evaluated respectively with the “Feeding Scale” (Chatoor et al., 1997) and with the “Play Scale” (Chatoor, 2006) and the socio-communicative abilities of children with a new social partner during play were evaluated with the “Early Social Communication Scales” (Mundy et al., 2003). We distinguished the dyads into two categories: dyads with functional interactions (high dyadic reciprocity, low dyadic conflict) and dyads with dysfunctional interactions (lower dyadic reciprocity, higher dyadic conflict). At T1, infants belonging to dyads with dysfunctional interactions were significantly lower in “Initiating Joint Attention” and in “Responding to Joint Attention” in interaction with a new social partner compared to the infants belonging to dyads with functional interactions. At T2, infants belonging to dyads with dysfunctional interactions were significantly lower in “Initiating Social Interactions” with a new social partner compared to the infants belonging to dyads with functional interactions. There were significant correlations between the quality of mother-infant interactions during feeding and infants’ social abilities in interaction with a stranger both at T1 and at T2. This study showed a stable relation over time between mother-child interactions and child’s social communicative skills in extra-dyadic interactions.